Pengaruh Disiplin Kerja terhadap Kinerja Staf pada Koperasi Credit Union (Cu) Sauan Sibarrung Kabupaten Tana Toraja - Desryani Pasada; Chrismesi Pagiu; Lisa K.Wibisono (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2023)
The aim of this research is to find out whether work discipline influences staff performance at the Sauan Sibarrung credit union (CU) cooperative, Tana Toraja Regency. The data collection procedure in this research was to distribute questionnaires distributed to 35 respondents taken from permanent staff at the Sauan Sibarrung Credit Union (CU) Cooperative, Tana Toraja Regency. Quantitative analysis of data with simple linear regression. Based on the results of the T test calculation on the work discipline variable, the calculated T result is (2.841) > (2.035). The results of this research indicate that the work discipline variable influences the performance of staff at the Sauan Sibarrung Credit Union (CU) cooperative, Tana Toraja Regency.